The role of US networks in Brazilian education: The New High School - Vaccari, Larissa; Vidal, Camila (Argumentum, 2026)
The reform of secondary education in Brazil, which established the ‘New High School’ (‘Novo Ensino Médio’ – NEM, in Portuguese), has brought about a series of changes in Brazilian schools, such as curriculum flexibilization and a focus on skills that reflect neoliberal discourse. These changes are aligned with the maintenance and perpetuation of capitalism and are closely connected to U.S. actors. In this context, this research seeks to identify the U.S. networks operating within the NEM and to understand how their actions contribute to maintaining the hegemonic power of the U.S. ruling class. The study relies on the analysis of documents related to the High School reform, the institutional websites of the private foundations involved, and the historic and social media profiles of their leading members. The results are presented through tables and network graphs created using the Gephi software, highlighting how the NEM is the outcome of the actions of a set of U.S. and Brazilian organisations, companies, financial institutions, universities, government agencies, and private foundations. In this regard, the Lemann Foundation and the Movimento pela Base stand out as two of the main nodes within these transnational networks.
Keywords: New High School; Transnational networks; United States; Hegemony